ІNSTRUMENTAL AND METHODOLOGICAL ASPECTS OF ART THERAPY IN MODERN EDUCATIONAL PRACTICE - Konovets, Svitlana (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article examines the essence and means of the phenomenon of "art therapy" and determines its possibilities in the modern educational process of domestic school and extracurricular educational institutions. The purpose of the article is to analyze the data obtained as a result of theoretical and empirical research to clarify the development of the necessary methodical material for implementation in practical pedagogical activity. To achieve the goal and objectives of the article, the following research methods were used: analysis of scientific and methodical literature on the research problem (for the purpose of comparing ideas, proposals, conclusions in the works of researchers with the obtained research results); questionnaires, observations, comparisons; analysis and generalization of the data obtained in the research process. The psychological, pedagogical, social, communicative, personal, creative, methodical aspects of art therapy are justified. The content of one of the popular and effective forms of “art therapy” – art photography – is characterized. The main functional features of artistic photography are revealed and analyzed (updating, objectifying, stimulating, expressive-cathartic, dynamic, meaningful, organizing (integrating), interactive). The possibilities of artistic photography are presented as means of enrichment of social, communicative, and patriotic experience widely used in the world educational practice through the manifestation of the creative potential of each growing personality. The conclusions emphasize that in the current conditions of martial law in our country, active implementation of forms and methods of art therapy should be carried out in modern educational institutions. At the same time, the implementation of the acquisition of skills and abilities by Ukrainian children and youth in various exercises of value-oriented, national-patriotic and creative education and purely peace-making means should be especially relevant.